2017
DOI: 10.1016/j.placenta.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Chorionic vascular “fit” in the human placenta: Relationship to fetoplacental outcomes

Abstract: Background Novel measures of the chorionic plate and vessels are used to test the hypothesis that variation in placental structure is correlated with reduced birth weight (BW) independent of placental weight (PW), suggesting functionally compromised placentas. Methods 917 mothers recruited to the Pregnancy, Infection and Nutrition Study delivering singleton live born infants at >30 gestational weeks had placentas collected, digitally photographed and weighed prior to formalin fixation. Beta (β) was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Similarly, Hauspurg et al found that the presence of placental maternal vascular malperfusion in healthy pregnancies was associated with increased risk of adverse outcomes in later pregnancies 18 . In a cohort study of over 900 pregnant women, Salafia et al found that placental disk size, including chorionic surface shape area and perimeter, was correlated with infant birth weight and gestational age at delivery 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hauspurg et al found that the presence of placental maternal vascular malperfusion in healthy pregnancies was associated with increased risk of adverse outcomes in later pregnancies 18 . In a cohort study of over 900 pregnant women, Salafia et al found that placental disk size, including chorionic surface shape area and perimeter, was correlated with infant birth weight and gestational age at delivery 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 2120 women found a relationship between placental surface area and weight, with uterine and umbilical blood flows, both of which are associated with fetal growth rate [ 8 ]. Another study of 916 women found correlations between the surface area of the chorionic plate and its perimeter with birth weight [ 9 ], suggesting that these comparatively simple measurements can identify suboptimal placental development. Although umbilical cord insertion is assumed to happen at the centre of the chorionic surface, a recent study found that the cord is actually not centred [ 7 ].…”
Section: Human Placental Morphologymentioning
confidence: 99%
“…In contrast to most permanent viscera that have more fixed shapes, the placenta is amoeboid and responds to intrauterine exposures by modifying its gross and microscopic structure and vascularization [16][17][18][19][20][21][22][23][24][25]. Shape variations that mark altered placental vascularization include irregularities of chorionic surface area, shape, thickness, and vascular patterning and cord insertion [26].…”
Section: Introductionmentioning
confidence: 99%